Weed Manager-A model-based decision support system for weed management in arable crops - Parsons, David J.; Benjamin, L. R.; Clarke, J.; Ginsburg, D.; Mayes, A.; Milne, Alice E.; Wilkinson, D. J. (Elsevier Science B.V., Amsterdam., 2009)
Weed Manager is a model-based decision support system to assist arable farmers and advisers in weed control decisions on two time scales: within a single season and over several years in a rotation. The single season decision is supported by a wheat crop and annual weed growth simulation, with a multi-stage heuristic decision model. The rotational aspect uses a model of seed population dynamics, with decisions optimised using stochastic dynamic programming. Each time scale has its own user interface within a single program integrated into the ArableDS framework, which provides data sharing between several decision support modules. Weed Manager was used by about 100 farmers and consultants in the 2005–2006 and 2006–2007 seas
Keywords: Weeds; Decision support; Models; Optimisation; Dynamic programming; Stochastic; Heuristics